Stakeholder Use and Feedback on Vaccination History and Clinical Decision Support for Immunizations Offered by Public Health - Rajamani, Sripriya (AMIA Annu Symp Proc, 2018)
National initiatives on Electronic Health Records (EHRs) recognize the vital role of public health and recommend reporting to Immunization Information Systems (IIS) and access of its clinical decision support for immunizations (CDSi). The objective of this study was to collect stakeholder feedback on access and utilization of CDSi from the Minnesota Immunization Information Connection (MIIC), Minnesota’s IIS. Input was solicited using a semi-structured questionnaire developed by experts, and from a sample of 17 key informants from February 2015 through May 2016. Analysis highlighted the appreciation of MIIC services, comprehensive vaccination history across providers and CDSi functionality, with public health users relying on MIIC. It also identified issues such as data entry due to read-only view, data quality and communications for improvement. These findings underscore the critical role of IIS, need to engage stakeholders, ensure CDSi updates, maintain good data quality, and promote bi-directional data exchanges across EHRs-IIS.